High performance organic/20 μm crystalline-silicon heterojunction solar cells. (18th June 2015) - He, Jian; Gao, Pingqi; Sheng, Jiang; Yang, Xi; Zhou, Suqiong; Ying, Zhiqin; Ye, Jichun
Abstract: Si/organic hybrid solar cells have attracted considerable attention as a promise long-range photovoltaic technique with low process cost and high power conversion efficiency. However, the consumption of a whole bulk silicon wafer in this kind of cells is obviously not cost-effective. Here, we report a flexible poly (3, 4-ethylene-dioxythiophene):polystyrenesulfonate/crystalline silicon (c-Si) heterojunction solar cell with substrate thickness of sub-20 μ m. The c-Si substrate has a nanopore surface texturing fabricated by a sample metal-assisted chemical etching process. In comparison to the non-textured thin c-Si cell, the nanopore-textured cell shows a 19.5% increase in J SC and a 40.2% increase in the efficiency. The inherent advantages of absorption improvement, p–n junction area increase, and carrier collection capability enhancement endow this nanopore-textured thin c-Si hybrid solar cell to approach an efficiency of 8.7%, as high as its bulk counterpart.